EFEKTIVITAS BAHAN AJAR LEARNING CYCLE 5E UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SEKOLAH DASAR - Laura Utami, Vira; Alpusari, Mahmud; Guslinda; Dwi Anggriani, Mitha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of 5E Learning Cycle-based instructional materials in improving elementary school students’ science process skills. This study utilized the Research and Development (R&D) method based on the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fifth-grade elementary school students in Pekanbaru. The research instruments consisted of science process skills tests administered as pretests and posttests. The data analysis techniques employed included a normality test, a paired-sample t-test, and N-Gain analysis. The results indicated that there was a significant difference between students’ pretest and posttest scores after using the 5E Learning Cycle-based instructional materials. Additionally, the N-Gain analysis results showed that the improvement in students’ science process skills fell into the moderate category. Thus, 5E Learning Cycle-based instructional materials are effective for improving the science process skills of elementary school students. The implications of this study suggest that the use of instructional materials designed according to the stages of the 5E Learning Cycle can support more active and meaningful learning and optimally develop students’ science process skills.